Expression of vascular endothelial growth factor receptor-2, epidermal growth factor receptor, cyclooxygenase-2, survivin, E-cadherin and Ki-67 in canine nasal carcinomas and sarcomas – a pilot study - Pauly, Ljuba Anna Maria; Junginger, Johannes; Oechtering, Gerhard Ulrich; Hewicker-Trautwein, Marion; Rösch, Sarah (Frontiers in Veterinary Science, 2024)
Background Malignant (intra-) nasal tumors (NTs) are the most common cause of chronic nasal discharge in dogs. Besides radiation therapy, palliative therapy is necessary in some dogs. Therefore, studies on receptor expression have supported the utility of tyrosine kinase inhibitors (TKI) in dogs with nasal carcinomas. However, studies on receptor expression in nasal sarcomas are lacking. Materials and methods This study evaluated the expression of vascular endothelial growth factor receptor-2 (VEGFR-2), epidermal growth factor receptor (EGFR), cyclooxigenase-2 (COX-2), Ki-67, survivin and E-cadherin in nasal carcinomas and sarcomas and compared it with tumor (T) categories based on computed tomography (CT). Results In 26 dogs with NTs, cross sectional imaging and upper airway endoscopy with guided biopsy collection were performed, followed by histopathological examination of NTs, revealing 19 epithelial and 7 mesenchymal tumors. While EGFR and E-cadherin were only expressed by carcinomas, the following markers were expressed by both carcinomas and sarcomas without significant differences between tumor types and T-categories: VEGFR-2 (carcinomas and sarcomas 100%), COX-2 (carcinomas 63%, sarcomas 57%), survivin (carcinomas 100%, sarcomas 86%) and Ki-67 (median expression of 28.5% in carcinomas and 17.3% in sarcomas). Conclusion Based on similarities in marker expression between canine carcinomas and sarcomas, clinical studies should further elucidate the use of TKI or COX-2 inhibitors as additional therapy in dogs with nasal sarcomas.